Use of Direct PCR Technique Without DNA Extraction in Confirmation Test for Salmonella typhimurium Bacteria on Meatball Samples - Alfi Sophian; Ratna Purwaningsih; Muindar Muindar; Eka Putri Juniarti Igirisa; Muhammad Luthfi Amirullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The use of direct PCR technique without DNA extraction in the confirmation test for Salmonella typhimurium ATCC 14028 bacteria on meatball samples was carried out in the Food and Drug molecular biology testing laboratory Administration in Gorontalo. The basis of this research is to have an impact on economic value in carrying out the confirmation test for S. typhimurium ATCC 14028, where testing is carried out conventionally, namely DNA extraction, which requires a large amount of money. Hence, it is necessary to innovate to modify the testing phase so that it is more effective and efficient. The purpose of this study was to see whether the direct PCR technique without DNA extraction can be done for the confirmation test of S. typhimurium ATCC 14028 on meatball samples. This study's sample consisted of 20 types of meatball samples spiked with S. typhimurium ATCC 14028 cultures. The method used in this study was qPCR analysis using the SYBR Green method. Data analysis was carried out based on 2 main criteria: (1) Ct analysis and (2) Tm analysis. Real-time PCR analysis results obtained Ct values ​​in the range 14.14 - 15.20 with an average of 14.82 and Tm values ​​85.20 - 86.30 with an average of 85.79. Based on these data, it can be concluded that using direct PCR can be used for testing confirmation of S. typhimurium ATCC 14028 on meatball samples.